The behaviour of logistic equation in fuzzy environment: fuzzy differential equation approach. Issue 1 (10th September 2021) - Mahata, Animesh; Matia, Sachindra Nath; Roy, Banamali; Alam, Shariful; Sinha, Hirak
Mathematical modelling on uncertainty in the field of biological science is progressively increasing to get more realistic outcome during the last few years. This article applies Hukuhara differentiable concept for solving FDE i.e., fuzzy differential equation. In this paper, we analyse the behaviour of logistic (Verhulst) model in imprecise environment particularly fuzzy environment. At first the logistic model form a fuzzy logistic model because of initial condition, co-efficient of the model and both initial condition and co-efficient contain fuzzy number, using generalised differentiable concepts this fuzzy logistic model is converted a system of crisp differential equation with a parameter α (0 ≤ α ≤ 1). Critical points and fuzzy stability of fuzzy logistic model are illustrated clearly. Suitable examples corresponding the model have been properly discussed in numerical discussion and also verified graphically.